Passive Dosimeter Based on BaBrF:Tm\(^{3+}\) Phosphor for \(γ\)-ray Dosimetry (Journal of Atomic, Molecular, Condensed Matter and Nano Physics, 2022)
Thulium (Tm\({}^{3+}\)) ions doped Barium Bromide Fluoride (BaBrF) samples were synthesized successfully through the solid-state diffusion method. The crystal structure and phase purity of the synthesized sample were examined by Powder X-Ray Diffraction (PXRD) analysis. Dosimetric properties of \(γ\)-ray exposed samples of BaBrF:Tm\({}^{3+}\) investigated. To obtain the maximum Thermoluminescence (TL) sensitivity of the material, the dopant concentration level and annealing temperature were optimized. It is observed that the dopant concentration 2.0 mol% of Tm\({}^{3+}\) and the annealing at 673 K temperature the phosphor material exhibits maximum TL intensity. The \(γ\)-Ray dose-response, fading of the TL signal, and kinetic parameters of the TL glow curve were also investigated. TL sensitivity of the BaBrF:Tm\({}^{3+}\) phosphor compared to the commercially available CaSO\({}_{4}\):Dy (TLD-900) dosimeter used for radiation measurement. On the basis of their promising dosimetric characteristics, it can become a good TL dosimeter for passive dosimetry of high energy \(γ\)-ray radiation.
Keywords: TLDs; Thermoluminescence; Dosimetry; Phosphor; Radiation